Management of infected non-unions of long bones using limb reconstruction system (LRS) fixator - Patra, Satya Ranjan; Kisan, Dasarath; Madharia, Divya; Panigrahi, Naresh Kumar; Samant, Saswat; Manoj, Medini; Shiv, Anmol; Das, Lalit Kumar (International Journal of Research in Orthopaedics, 2017)
Background: Due to increasing number of high-energy traumatic events, the incidence of complex and compound fractures are also in the rise. Such fractures are often exposed to various environmental contaminants, inadequate debridement and sometimes erroneous decision making leading to cases of infected nonunions. Eradication of infection in such cases and achieving union may sometimes pose serious challenge to orthopaedic surgeons. Presence of comminution, bone gap or deformity can seriously complicate the situation. No definite surgical technique has been found to be full proof in dealing with these infected nonunion cases. In this scenario the limb reconstruction system (LRS) fixator is emerging as a useful option for infected nonunions with deformity or gap nonunion. Methods: Twenty seven cases of infected nonunions involving tibia (n=19), femur (n=7) and humerus (n=1) were treated by LRS fixators after debridement of the infected nonunion site. Flap cover procedure was done as per necessity. Bone gaps and limb length discrepancies were dealt with bone transport or limb lengthening by the LRS instrument. Weight-bearing and removal of fixator was decided according to the radiological evidence of healing. Results: All the nonunions and the regeneration sites healed uneventfully, although the union time was varied (range, 21-52 weeks). Commonest complication was pin-tract infection and pain. The mean lower extremity functional score (LEFS) was 60.3 out of 80. Conclusions: LRS fixator is an excellent tool for management of infected nonunions which is easy to apply, comfortable for the patient with minimum complications and predictable as well as reproducible outcomes.